2017
DOI: 10.3389/fendo.2017.00119
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune Thyroiditis and Glomerulopathies

Abstract: Autoimmune thyroiditis (AIT) is generally associated with hypothyroidism. It affects ~2% of the female population and 0.2% of the male population. The evidence of thyroid function- and thyroid autoantibody-unrelated microproteinuria in almost half of patients with AIT and sometimes heavy proteinuria as in the nephrotic syndrome point to a link of AIT with renal disease. The most common renal diseases observed in AIT are membranous nephropathy, membranoproliferative glomerulonephritis, minimal change disease, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
24
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 61 publications
(63 reference statements)
2
24
1
2
Order By: Relevance
“…This may be partly due to the different methodology (retrospective study versus prospective study). Previous studies have indicated that HT was the most common cause of hypothyroidism ( 45 ), but in our study, the autoantibodies level of patients classified to hypothyroidism group was normal, so the different diagnostic criteria for hypothyroidism, which might explain the different findings ( 16 , 44 ) to some extent.…”
Section: Discussioncontrasting
confidence: 67%
“…This may be partly due to the different methodology (retrospective study versus prospective study). Previous studies have indicated that HT was the most common cause of hypothyroidism ( 45 ), but in our study, the autoantibodies level of patients classified to hypothyroidism group was normal, so the different diagnostic criteria for hypothyroidism, which might explain the different findings ( 16 , 44 ) to some extent.…”
Section: Discussioncontrasting
confidence: 67%
“…From the clinical point of view, the majority of the cases reported to date were nephrotic syndrome rather than reduced eGFR (for review, see Santoro et al 2017 ). With regard to the relationship between pathological and clinical findings, the most informative contribution has been provided by Koçak et al ( 2012 ) who reviewed retrospectively 28 patients with Hashimoto’s thyroiditis referred to their department because of unexplained haematuria, proteinuria or renal impairment.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, vasculitis or cross-reactivity between antigens are among the mechanisms suggested to explain the cases of glomerulopathies associated with autoimmune thyroiditis (Santoro et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…reported differently according to each autoimmune disease 2 . Given that AAV is one of the systemic autoimmune diseases affecting most major organs 3 , and there is cross-reactivity between thyroid peroxidase and myeloperoxidase (MPO) molecules 4 , the prevalence of thyroid dysfunction, including autoimmune thyroiditis, may be increased in patients with AAV.…”
mentioning
confidence: 99%